A Novel Mechanism for Small Heat Shock Proteins to Function as Molecular Chaperones - Zhang, Kaiming (Sci Rep, 2015)
Small heat shock proteins (sHSPs) are molecular chaperones ubiquitously present in all forms of life, but their function mechanisms remain controversial. Here we show by cryo-electron microscopy and single particle 3D reconstruction that, at the low temperatures (4–25°C), CeHSP17 (a sHSP from Caenorhabditis elegans) exists as a 24-subunit spherical oligomer with tetrahedral symmetry. Our studies demonstrate that CeHSP17 forms large sheet-like super-molecular assemblies (SMAs) at the high temperatures (45–60°C), and such SMAs are apparently the form that exhibits chaperone-like activity. Our findings suggest a novel molecular mechanism for sHSPs to function as molecular chaperones.